2013
DOI: 10.1103/physreve.87.042905
|View full text |Cite
|
Sign up to set email alerts
|

Chiral symmetry breaking in a reaction-diffusion system

Abstract: The emergence of order in far-from-equilibrium systems is often accompanied by the formation of spatially asymmetric patterns. About 30 years ago, a general mechanism to select a chiral solution by coupling a reaction-diffusion system to an external chiral electric field was proposed by Nicolis and Prigogine [Proc. Natl. Acad. Sci. USA 78, 659 (1981)]. However, no experimental or even numerical evidence in reaction-diffusion systems has been reported yet. Here we report a chiral symmetry-breaking phenomenon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…For example, in the complex Ginzburg-Laudau equation (CGLE) with a broken chiral symmetry breaking term, Nam et al 33 showed that this chiral term would cause a shift in the frequency of spiral waves and the sign of this shift depends on the chirality of the spiral waves. In our recent work 38 , such chirality-dependent frequency response was also observed in RD systems coupled to the CPEF. However, a quantitative description of the chirality-dependent frequency response to the CPEF in such RD systems is still lacking.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…For example, in the complex Ginzburg-Laudau equation (CGLE) with a broken chiral symmetry breaking term, Nam et al 33 showed that this chiral term would cause a shift in the frequency of spiral waves and the sign of this shift depends on the chirality of the spiral waves. In our recent work 38 , such chirality-dependent frequency response was also observed in RD systems coupled to the CPEF. However, a quantitative description of the chirality-dependent frequency response to the CPEF in such RD systems is still lacking.…”
Section: Introductionsupporting
confidence: 52%
“…Recently, a circularly polarized electric field (CPEF) that possesses chirality was theoretically proposed 34 and was implemented in the BZ experiment 35 , which allows us to study the response of spiral waves to a chiral electric field in RD systems. Indeed, it has been shown that the CPEF has some pronounce effects on spiral waves [36][37][38] that were not observed in RD systems subject to achiral fields such as a dc or ac electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a circularly polarized electric field (CPEF) that possesses chirality was theoretically proposed 34 a) Electronic mail: bwli@hznu.edu.cn and was implemented in the BZ experiment, 35 which allows us to study the response of spiral waves to a chiral electric field in RD systems. Indeed, it has been shown that the CPEF has some pronounce effects on spiral waves [36][37][38] that were not observed in RD systems subject to achiral fields such as a dc or ac electric field.…”
Section: Introductionmentioning
confidence: 99%
“…41 In Rayleigh-Bénard convection, chiral symmetry breaking in spiral-defect populations was observed when the system rotated along the vertical axis, and the chirality of the dominant spirals relies on the rotation sense of the system. 32 By subjecting a RD system to the CPEF, 38 we recently found that the zero-rotation chiral symmetry between CW and CCW spiral defects breaks and that ordered spiral waves with preferred chirality arise from the spiral turbulence state. Here too, the preferred chirality was only determined by the chirality of the CPEF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation